Calcium in the production and quality of cauliflower seeds (Research, Society and Development, 2021)
There are researches with calcium to produce the cauliflower inflorescence, but for seeds production no studies were found, this element is fundamental for the fixation of the floral buds and in the production and quality of seeds. The objective was to evaluate the effect of foliar application of calcium on different phenological stages of cauliflower plants in seed production and quality. Eleven treatments were evaluated, varying the number (1 to 4) of calcium (6 g L-1 of calcium chloride) applications and the phenological stages (E1 = floral stem with 30 cm length, E2 = opening of the first flowers; E3 = formation of first siliques; E4 = 50% of silique formed), resulting: T1 = control without application of Ca; T2 = E1; T3 = E1 + E2; T4 = E1 + E2 + E3; T5 = E1 + E2 + E3 + E4; T6 = E2; T7 = E2 + E3; T8 = E2 + E3 + E4; T9 = E3; T10 = E3 + E4; T11 = E4. The results showed a higher seed production per plant in treatments T10 (E3 + E4) and T11 (E4) with 42 and 48 g per plant, and a higher number of seeds per plant, with 12,379 and 12,978, respectively, compared to the control (T1): 23 g and 5,725 seeds per plant. Calcium applications in different phenological stages did not influence the physiological quality (germination and vigor) of cauliflower seeds of cultivar 'Piracicaba Precoce'. Application of these treatments in other cultivars is promising for further studies.